2011
DOI: 10.1113/jphysiol.2011.210930
|View full text |Cite
|
Sign up to set email alerts
|

Purinergic modulation of preBötzinger complex inspiratory rhythm in rodents: the interaction between ATP and adenosine

Abstract: Non-technical summary Hypoxia causes an increase in breathing followed by a secondary depression that is most pronounced, and potentially life-threatening, in premature infants. Adenosine triphosphate (ATP) is released in brainstem respiratory networks during hypoxia, where it attenuates the secondary respiratory depression. Mechanisms are unknown but likely to be complex because ATP is degraded by enzymes into ADP, which is excitatory, and adenosine (ADO), which is inhibitory. We demonstrate in mouse, like ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
71
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(75 citation statements)
references
References 80 publications
4
71
0
Order By: Relevance
“…Ruangkittisakul and Ballanyi, 2010;Zwicker et al, 2011). The latter findings indicate a species difference for ADO effects for both rhythmogenic cranial inspiratory and spinal locomotor CPGs because ADO (modestly) inhibits both systems in newborn mice in vitro (Zwicker et al, 2011;Witts et al, 2012). In the following, we discuss our findings regarding the literature for interstitial ADO levels and putative mechanisms involved in the A 1 receptor-mediated ADO effects on newborn rat lumbar CPGs revealed here.…”
Section: Comparison With Ado Effects On Other Vertebrate Locomotor Cpgsmentioning
confidence: 78%
See 2 more Smart Citations
“…Ruangkittisakul and Ballanyi, 2010;Zwicker et al, 2011). The latter findings indicate a species difference for ADO effects for both rhythmogenic cranial inspiratory and spinal locomotor CPGs because ADO (modestly) inhibits both systems in newborn mice in vitro (Zwicker et al, 2011;Witts et al, 2012). In the following, we discuss our findings regarding the literature for interstitial ADO levels and putative mechanisms involved in the A 1 receptor-mediated ADO effects on newborn rat lumbar CPGs revealed here.…”
Section: Comparison With Ado Effects On Other Vertebrate Locomotor Cpgsmentioning
confidence: 78%
“…For quantification of these Results, see Table 4. Ruangkittisakul and Ballanyi, 2010;Zwicker et al, 2011). The latter findings indicate a species difference for ADO effects for both rhythmogenic cranial inspiratory and spinal locomotor CPGs because ADO (modestly) inhibits both systems in newborn mice in vitro (Zwicker et al, 2011;Witts et al, 2012).…”
Section: Comparison With Ado Effects On Other Vertebrate Locomotor Cpgsmentioning
confidence: 83%
See 1 more Smart Citation
“…Recent data indicated that ionotropic glutamate and P2X receptors in the rostral ventrolateral medulla of the Bötzinger complex play roles in opposite directions in the control of respiratory responses to chemoreflex activation in awake rats (Moreaes et al, 2011). It has been shown in rodents that the ATP-adenosine balance is a determining factor in the purinergic modulation of the PBC inspiratory rhythm and that the underlying pathways seem to differ between mice and rats (Zwicker et al, 2011). Another article showed that the chemosensitive regions of the ventrolateral medulla were immunoreactive for the P2X2 receptor, which mediates ATP potentiation of respiratory discharge frequency (Lorier et al, 2004).…”
Section: Central Control Of Respirationmentioning
confidence: 99%
“…This response is independent of the carotid bodies and is largely mediated by the activation of the barosensitive neurons of the RVLM including the C1 cells (47, 48, 67, 180). Their depolarization, like that of the pre-Bötzinger complex, could be partly a cell-autonomous response, for example, an increase in persistent sodium current or calcium permeability (69,136) or could result from the release of gliotransmitters such as ATP (65,115,169,181,202). Reis and collaborators championed the idea that the C1 cells are oxygen sensors, implying that these neurons are activated by small "physiologically relevant" reductions in brain PO 2 and then trigger countervailing responses including an increase in AP and a neurogenic rise in cerebral blood flow without concomitant change in brain metabolism (180).…”
Section: C1 Neurons and Responses To Hypoxiamentioning
confidence: 99%